2014
DOI: 10.3892/ijo.2014.2298
|View full text |Cite
|
Sign up to set email alerts
|

The expression of Claudin 1 correlates with β-catenin and is a prognostic factor of poor outcome in gastric cancer

Abstract: Abstract. Claudin 1 is one of the tight junction proteins, which are critical in the maintenance of epithelial integrity. Aberrant regulation of CLDN1 and its correlation with β-catenin have been discovered in malignant tumors. The present study aimed to investigate the expression profile and clinical relevance of CLDN1 and β-catenin. The protein levels of CLDN1 and β-catenin were examined using immunohistochemical staining. The characteristics of expression profile and prognostic value were analyzed using Pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 39 publications
5
30
0
Order By: Relevance
“…In contrast, Wu et al [14] reported that claudin-1 expression in invasive front was different from that in the mucosa of gastric cancer, and that the claudin-1 up-regulation in invasive front was positively related with the differentiated degree, and with the invasiveness and metastasis of gastric adenocarcinoma. Huang et al [26] showed that claudin-1 expression was increased in tumor tissues that were of intestinal type, differentiated type, at an advanced TNM stage and with lymph node metastasis. Their results are consistent with our findings which showed loss of claudin-1 in diffuse type gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Wu et al [14] reported that claudin-1 expression in invasive front was different from that in the mucosa of gastric cancer, and that the claudin-1 up-regulation in invasive front was positively related with the differentiated degree, and with the invasiveness and metastasis of gastric adenocarcinoma. Huang et al [26] showed that claudin-1 expression was increased in tumor tissues that were of intestinal type, differentiated type, at an advanced TNM stage and with lymph node metastasis. Their results are consistent with our findings which showed loss of claudin-1 in diffuse type gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CLDN-1 is highly expressed in gastric cancers [108,109]. High expression of CLDN-1 was reported in intestinal type gastric cancer that correlated with lymph node metastasis, advanced TNM (classification of malignant tumors) stage, recruitment, and activation of MMP-2 and MMP-9, which are all responsible for enhanced cell invasion and metastasis [60,109].…”
Section: Claudin-1 and Gastric Cancermentioning
confidence: 99%
“…CLDN-1 is highly expressed in gastric cancers [108,109]. High expression of CLDN-1 was reported in intestinal type gastric cancer that correlated with lymph node metastasis, advanced TNM (classification of malignant tumors) stage, recruitment, and activation of MMP-2 and MMP-9, which are all responsible for enhanced cell invasion and metastasis [60,109]. The invasion of gastric adenocarcinoma cells is associated with the levels of CLDN-1 expression as CLDN-1 is found to be upregulated in gastric carcinoma and participates in the metastatic behavior of these cancer cells [45].…”
Section: Claudin-1 and Gastric Cancermentioning
confidence: 99%
“…For CLDN1, its overexpression in gastric cancer is related with tumor invasion and metastasis [ 15 , 16 ]. We recently reported that CLDN1 was highly expressed in intestinal-type gastric cancer and correlated with advanced TNM stage, lymph node metastasis and poor outcome [ 17 ]. However, the role and detailed mechanism of CLDN1 in gastric cancer are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Integrity of cell-cell contacts prevents anoikis involving survival signal pathways activation of β-catenin, Src and PI3-K/Akt [ 23 , 28 ]. Indeed, there is a mutual interaction between CLDN1 and β-catenin [ 17 , 27 , 29 ]. The role of CLDN1 and β-catenin in the gastric tumorigenesis and metastasis piqued our interest in the further study.…”
Section: Introductionmentioning
confidence: 99%